Cadherin-related protein 24 induces morphological changes and partial cell polarization by facilitating direct cell-cell interactions - Rizk, Sandra (2012)
Cadherin-related protein 24 (CDHR24) is a potential tumor suppressor located apically as well as laterally in polarized cells. Here, the role of CDHR24 in contributing to cell morphology and polarity is examined. CDHR24 was predominantly localized at the nonattached part of nonpolarizing cells while another apically sorted protein, aminopeptidase N, was equally distributed over the plasma membrane. Furthermore, CDHR24 expression induced cell aggregation capacity, indicating direct cell-cell interaction. The transepithelial resistance, however, was elevated in polarized MDCK cells, but not in nonpolarizing CHO cells. Our data propose a model in which CDHR24 is directly involved in cell and tissue morphogenesis.